2006
DOI: 10.1073/pnas.0511234103
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriorhodopsin (bR) as an electronic conduction medium: Current transport through bR-containing monolayers

Abstract: Studying electron transport (ET) through proteins is hampered by achieving reproducible experimental configurations, particularly electronic contacts to the proteins. The transmembrane protein bacteriorhodopsin (bR), a natural light-activated proton pump in purple membranes of Halobacterium salinarum, is well studied for biomolecular electronics because of its sturdiness over a wide range of conditions. To date, related studies of dry bR systems focused on photovoltage generation and photoconduction with multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
161
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(171 citation statements)
references
References 35 publications
(40 reference statements)
10
161
0
Order By: Relevance
“…Despite this, recent analyses have concluded that the lipidated protein can sustain current magnitudes comparable to those observable with conjugated organics of comparable length. 30 The probe-independent observations we report herein not only highlight the role of the retinal moiety in mediating electronic conductance through BR 20 but also the significance of partial delipidation in facilitating a more robust coupling of this conduit to electrodes. The combined effects of partial delipidation and chemisorption on BR electrical properties, long-term stability and on the different intermediates of its photocycle are currently under study.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Despite this, recent analyses have concluded that the lipidated protein can sustain current magnitudes comparable to those observable with conjugated organics of comparable length. 30 The probe-independent observations we report herein not only highlight the role of the retinal moiety in mediating electronic conductance through BR 20 but also the significance of partial delipidation in facilitating a more robust coupling of this conduit to electrodes. The combined effects of partial delipidation and chemisorption on BR electrical properties, long-term stability and on the different intermediates of its photocycle are currently under study.…”
mentioning
confidence: 87%
“…20−22 Attempts to engage monolayers of BR in the native PM for electronic measurements, through the use of either lithographically fabricated contacts or C-AFM probes, have led to reported junction resistances in the TΩ range 23 and low (pA range) currents per trimer. 20,23,24 The photoactivity of BR is retained in dried films of PM, 25,26 making it an attractive material for developing biomolecular devices, such as photodetectors or optical memories. 7,27,28 In all previous work, to the best of our knowledge, the protein photoresponse has been analyzed in the PM, within relatively large (micrometer sized) patches or in PM dispersions contained in wells.…”
mentioning
confidence: 99%
“…All of these results seem to be inconsistent with previous experiments' conclusions that the single-stranded helical molecules, such as ssDNA, may not polarize the electrons (5). We note that the electron transport/transfer has been widely investigated in many proteins (19)(20)(21)(22)(23)(24)(25)(26). However, to our knowledge, the underlying physics is still unclear for spin-selective phenomenon observed in the α-helical protein and for the contradictory behaviors between the protein and the ssDNA.…”
mentioning
confidence: 99%
“…BR possesses an extremely stable hexagonal lattice structure, and is resistant against chemical, thermal and photochemical degradation [68], which makes it a potentially optimal biomaterial for use in biological devices under conditions of high temperature, strong light intensity and high ionic strength. More importantly, the optical properties of BR, and its ability to form two-dimensional films are being investigated for use in optical nanodevices, including exploitation of the photochromic properties of BR, which mainly involves interchange of the initial B and M states.…”
Section: Biotechnological Potentialsmentioning
confidence: 99%
“…The light-adapted form contains only all-trans retinal whereas the dark-adapted form contains equal amounts of 13-cis and all-trans retinal. Both forms go through a cyclic photoreaction, but only the all-trans retinal-containing BR translocates protons across the membrane [67,68]. Briefly, proton translocation by BR can be described as follows.…”
Section: Retinal Proteinsmentioning
confidence: 99%